2011
DOI: 10.1167/iovs.10-6644
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Falls, Injurious Falls, and Other Injuries Resulting from Visual Impairment among Older Adults with Age-Related Macular Degeneration

Abstract: Among older adults with AMD, increased visual impairment was significantly associated with an increased incidence of falls and other injuries. Reduced contrast sensitivity was significantly associated with both increased rates of falls and other injuries, while reduced visual acuity was only associated with increased fall rate. These findings have important implications for the assessment of visually impaired older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 43 publications
4
120
3
1
Order By: Relevance
“…The odds ratios for two or more falls in the past year for patients with poor vision were 2.02 (95% CI, 1.13-3.63) for current binocular acuity and 1.85 (95% CI, 1.10-3.12) for visual sensitivity [52]. Wood et al found that 74% of patients with AMD reported sustaining a fall or non-fallrelated injury (e.g., lacerations or collisions with an object), while 30% of patients reported more than one fall [54].…”
Section: Fallsmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds ratios for two or more falls in the past year for patients with poor vision were 2.02 (95% CI, 1.13-3.63) for current binocular acuity and 1.85 (95% CI, 1.10-3.12) for visual sensitivity [52]. Wood et al found that 74% of patients with AMD reported sustaining a fall or non-fallrelated injury (e.g., lacerations or collisions with an object), while 30% of patients reported more than one fall [54].…”
Section: Fallsmentioning
confidence: 99%
“…Reduced contrast sensitivity has been shown to be the strongest predictor of falls and other injuries in patients with AMD [54] Melillo et al developed a classification tree to help ophthalmologists and optometrists identify patients at high-risk of falling within 1 year [57]. Once high-risk patients have been identified, healthcare professionals should refer patients to rehabilitation specialists for guidance on interventions and modifiable risk factors such as exercise [58,59], video game technology [59,60], appropriate footwear, floor coverings, and hip protectors [61] to reduce the incidence of falls and the risk of injury.…”
Section: Fallsmentioning
confidence: 99%
“…Fear in this group was also related to an inability to detect the correct buttons to push, as pushing the wrong button may lead to fire or accidents. In addition, Wood et al (2011) revealed that there is a positive relationship between home accidents and visual impairment in older people.…”
Section: Literature Review 21 Home Hazards Accidents and Fallsmentioning
confidence: 99%
“…Age-related hearing impairment is correlated with Alzheimer disease, and reduced hearing can contribute to falls and fractures [18], greater dependence on others, and loneliness [19][20][21]. For those who have ailments and chronic diseases, hearing impairments constitute an additional negative factor to the other problems and perhaps an unnecessary burden, which may lead to the later part of life being more troublesome than necessary [11,22].…”
Section: Introductionmentioning
confidence: 99%